Analysis of the Impact of Corporate Governance Mechanisms on Earnings Management: A Study of Pharmaceutical Companies from 2019 to 2024 - Firman Syah; Vidyarto Nugroho (Green Publisher Indonesia, 2026)
This research aimed to analyze the influence of corporate governance mechanisms on earnings management in pharmaceutical companies listed on the Indonesia Stock Exchange (IDX) during the 2019–2024 period. The corporate governance mechanisms examined in this study were proxied by audit committee size, audit committee expertise, and board of directors’ size. Using a quantitative approach with secondary data obtained from annual reports and financial statements, the sample consisted of 9 pharmaceutical companies selected through purposive sampling, resulting in 54 panel observations. Data analysis was conducted using panel data regression with cluster-robust standard error estimation to improve the reliability of the test results. Earnings management was measured using the Modified Jones Model through discretionary accruals. The results showed that audit committee size, audit committee expertise, and board of directors’ size did not have a significant effect on earnings management. These findings indicate that the structural corporate governance mechanisms examined in this study were not effective in limiting or explaining earnings management practices in pharmaceutical companies during the observation period. This suggests that the effectiveness of corporate governance is determined not only by structural characteristics but also by other factors, such as supervisory independence, audit quality, company-specific characteristics, and business environment conditions. Future research is encouraged to expand the sample size, include additional corporate governance variables, and apply alternative earnings management measurement models to obtain more comprehensive findings.